Purification and characterization of a pilin specific for Brazilian purpuric fever-associated Haemophilus influenzae biogroup aegyptius (H. aegyptius) strains. - Weyant, R S (1990)
Brazilian purpuric fever (BPF) is a recently described fatal pediatric disease caused by systemic infection with Haemophilus influenzae biogroup aegyptius. Previous studies have shown that all H. influenzae biogroup aegyptius strains isolated from BPF cases and case contacts share several unique phenotypic and genotypic characteristics that differentiate them from other H. influenzae biogroup aegyptius strains isolated from conjunctivitis cases in Brazil. One key characteristic of this BPF clone is reactivity in a BPF-specific monoclonal antibody enzyme-linked immunosorbent assay. We have purified and partially characterized a pilin, referred to as the 25-kilodalton (kDa) protein. Aggregates of this protein contain a heat-labile epitope which is recognized by a monoclonal antibody used in the BPF-specific enzyme-linked immunosorbent assay. The protein has a molecular weight of approximately 25,000, is insoluble in most detergents, and fractionates with outer membrane vesicles after LiCl extraction. Biochemical analysis of the 25-kDa protein shows it to have an amino acid composition similar but not identical to that of the H. influenzae type b pilin. The sequence of 20 N-terminal amino acids of the 25-kDa protein shows almost complete homology with the N terminus of the H. influenzae type b pilin and the types 1 and P pilins of Escherichia coli. Transmission electron microscopic analysis of the purified protein shows the presence of filamentous structures similar in morphology to those of H. influenzae pili. Reactivity between the 25-kDa protein and the BPF-specific monoclonal antibody is demonstrated by Western blotting (immunoblotting) and colloidal gold-enhanced immunoelectron microscopy. Hemadsorption analysis shows that expression of this protein is associated with increases in piliated cells and enhanced binding of these cells to human erythrocytes. These studies indicate that expression of the 25-kDa protein is a characteristic unique to the BPF clone and suggest that this protein plays a role in the pathogenesis of BPF.